Prospects for the idea of Knowledge-Based Economy. Employing the ancient perspective for the development of the future - Ceglarska, Anna; Cymbranowicz, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
One of the most prevalent concepts describing the modern economy is the Knowledge-Based Economy (KBE). In an era of rapid scientific and technological advancement, the value of knowledge cannot be overstated; it is our most valuable resource. The aim of this paper is to examine the genesis and evolution of the KBE, as well as highlighting potential challenges and opportunities for its future. Paraphrasing F. Fukuyama’s famous prediction of ‘the end of history’, it seems reasonable to ask whether the KBE marks the ‘end of the economy’ or whether new determinants may emerge to transform it. Furthermore, as new theories emerge, the question arises as to which of them, and why, should be recognised as ‘knowledge’ and thus developed to shape the future. Rather than analyzing modern theories, we propose a return to the foundations of our cultural and intellectual heritage. Therefore, this study employs critical literature analysis and philosophical inquiry, referencing contemporary economic thought and Aristotelian hermeneutics. The terminological debates are limited in order to focus on the cultural and historical dimensions of KBE and to suggest its potential future trajectory. Drawing on Aristotle and the metaphor of the ‘ship of state’, we argue that nowadays, it is no longer sufficient to collect and analyse facts; rather, there is a need to assess probabilities and discuss potential outcomes. Translating this ability into action would enable us to make our knowledge ‘practical’ (in Aristotelian sense), and thus assist in charting a course for the future.

Jednym z najczęściej używanych we współczesnej nauce o gospodarce terminów jest „gospodarka oparta na wiedzy” (GOW). W dzisiejszych czasach, kiedy obserwujemy szybki rozwój nauki i technologii, znaczenie wiedzy staje się kluczowe, gdyż jest ona jednym z naszych najcenniejszych zasobów. Celem tego artykułu jest zbadanie genezy oraz ewolucji koncepcji GOW, a także omówienie wyzwań, które mogą stanąć przed nią w przyszłości. W tym kontekście warto, parafrazując słynną prognozę F. Fukuyamy o „końcu historii”, zadać pytanie, czy GOW będzie stanowić ostateczny etap rozwoju gospodarki, czy też pojawią się nowe czynniki, które zmodyfikują jej oblicze. Trzeba też się zastanowić, które z nowych teorii naukowych zasługują na miano „wiedzy” i tym samym powinny być rozwijane. Zamiast bazować na klasycznej analizie obecnych koncepcji gospodarczych, proponujemy powrót do fundamentów naszego dziedzictwa intelektualnego i kulturowego. Dlatego też niniejsze badanie wykorzystuje krytyczną analizę literatury i dociekania filozoficzne, odwołuje się do współczesnej myśli ekonomicznej i hermeneutyki Arystotelesa. Rozważania terminologiczne zostały ograniczone, by skupić się na kulturowych i historycznych wymiarach GOW i zasugerować jej potencjalne drogi rozwoju. Odwołując się do myśli Arystotelesa i antycznej metafory porównującej państwo do okrętu, twierdzimy, że dziś nie wystarczy już wiedza oparta na gromadzeniu i analizie danych, lecz konieczna jest również umiejętność uwzględniania prawdopodobieństw i przewidywania potencjalnych rezultatów. Zastosowanie tej umiejętności w działaniu umożliwi stworzenie wiedzy „praktycznej” (w sensie arystotelesowskim), a tym samym może pomóc w wyznaczaniu kursu rozwoju i działań na przyszłość.
Keywords: knowledge; economy; Aristotle; philosophy; education; wiedza; gospodarka; Arystoteles; filozofia; edukacja